Miele Limone (Materiali di Estetica. Terza serie, 2024)
The author examines the intricate mother-daughter relationship, emphasizing its psychological and evolutionary complexities. She explores how this bond, characterized by deep ambivalence and a blend of conflict and care, profoundly influences both personal growth and identity formation. The essay underscores the challenges and dynamics of navigating emotional autonomy while maintaining familial connections.
Keywords: mother-daughter relationship; emotional autonomy; familial bonds; psychological development